Demonstration of Collaborative Features of Remote Laboratory NetLab - Nedic, Zorica (International Journal of Online and Biomedical Engineering (iJOE), 2013)
In this presentation we would like to demonstrate collaborative aspects the remote laboratory NetLab. Many universities worldwide have developed remote laboratories that are now common part of laboratory component used by their students. NetLab is one of them, and is used by undergraduate students to perform experiments on electrical circuits. Unlike majority of other laboratories NetLab is from the beginning designed as an interactive collaborative environment where a number of students can access the equipment remotely from different places in the world and collaboratively wire circuits, connect and set up instruments and perform measurements. All users that are logged on concurrently have the full control of the system. Because NetLab is an interactive learning environment students are required to coordinate their actions. Unlike in a real laboratory where students see what everyone is doing, collaboration in remote laboratory is not a trivial task. To enable this collaboration NetLab has a number of features to support interactive collaborative work. In the proposed session these features will be demonstrated.